Interethnic relations and conflict potential of the student youth in the vocational education system of Kazakhstan - Shormanbayeva, Dinara; Shebalina, Olga; Smirnova, Galina; Sharipova, Rufina; Gotting, Valentina (International Journal of Innovative Research and Scientific Studies, 2025)
This article explores the dynamics of interethnic relations among students in Kazakhstan—a group particularly receptive to social changes, global challenges, and vulnerable during the critical stage of value formation. The research is especially relevant in the context of a multicultural educational environment, which serves as the foundation for this study. The aim is to assess the current state of interethnic interactions among students and identify key factors that shape them. A large-scale survey highlighted important influences, including social well-being, interethnic relationships, and the potential for conflict, defined as hostility linked to ethnic identity, as well as migration-related sentiments among young people. By employing a model developed with PLS Softer software, the study uncovered connections between these factors. The findings reveal consistent patterns within the university setting, where a lack of ethnic diversity in the academic and social environment impacts the stability of interethnic relationships. The article also offers practical recommendations for creating a supportive environment for interethnic communication, both in the classroom and through extracurricular activities in higher education.